Does urban–rural integration contribute to environmental health? Exploring the interplay between urban–rural integration and air quality dynamics in Yangtze River middle reaches city cluster - Jixin Yang; Jixin Yang; Bowen Fu; Bowen Fu; Xufeng Cui; Xufeng Cui (Frontiers in Public Health)
BackgroundExploring the coordinated relationship between urban–rural integration and air quality has significant implications for promoting urban–rural development, preventing air pollution and ensuring residents’ health. This study takes Yangtze River middle reaches city cluster as a case study, calculates the levels of urban–rural integration and air quality development, analyzes their coupled coordination relationship and driving factors, and explores the path of coordinated development.MethodsThis study constructs a coupling coordination degree model to analyze the relationship between the urban–rural integration development level and air quality development level. We use the trend surface method to analyze the spatial divergence characteristics of the coordination degree between urban–rural integration and air quality. In addition, we used a geographic detector to analyze the factors affecting the coordination degree.Results(1) The overall level of urban–rural integration development showed an upward trend. High-value regions were concentrated in the Wuhan, Chang-Zhu-Tan, and Nanchang metropolitan areas. (2) The Air Quality Index showed an overall decline, with the most significant improvements observed in Wuhan, Changsha, and Jiujiang. (3) The coupling degree increased from 0.570 in 2013 to 0.794 in 2021, and the coordination degree increased from 0.337 in 2013 to 0.591 in 2021. The link between urban–rural integration and air quality has deepened over time, and the two promote each other, making city cluster develop towards environmental friendliness. The spatial distribution of coordination degree shows a “high in the west and low in the east, high in the north and low in the south” trend. (4) Per capita GDP, non-agricultural employment ratio, urban–rural spatial circulation media, population urbanization level, and fixed asset investment were identified as the core factors driving the coordination degree between urban–rural integration and air quality.ConclusionThis study confirms that the urban–rural integration and air quality of Yangtze River middle reaches city cluster are gradually changing in the direction of high-quality coordination. However, there are great differences among cities, regional imbalance is prominent, and coordination degree is driven by multidimensional factors.